EFEK ANTIINFLAMASI EKSTRAK AIR SARANG BURUNG WALET (Collocalia fuciphaga Thunberg, 1812) PADA MENCIT (Mus musculus L. 1758) YANG DIINDUKSI KARAGENAN - , FITRI NUROINI, Dr. biol. hom. Nastiti Wijayanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Swiftlets Collocalia fuciphaga constructed their nest with salivary glue. The nest is white and called Edible Birdâs Nest (EBN). The major component of EBN is glycoproteins that consist of sialic acid (9 %), N-acetylgalactosamine (7.2 %), N-acetylglucosamine (5.3 %), galactose (16.9 %) and fructose (0.7 %). Glycoprotein is an important molecule in the regulation of the immune system, increase cell proliferation and decrease the production of TNF-Î±. The aims of this study was to determine the anti-inflammatory effect of EBN swiftlet C. fuciphaga in the expression of TNF-Î±, histological and integumentum feet thick, total leukocyte count and leukocyte differential count. Research design using Randomized Complete Design (RCD) with 6 treatment and 4 replication. The treatment are normal control, negative control, antiinflammation control group and 3 group treatment with EBN extract (0.1, 1 and 10 mg/ 20 g W. EBN was given orally and after an hour each group were injected subcutaneously with 0.05 ml of 1 % carrageenan in 0.9 % NaCl on the right foot mice. The results showed that administration of oral EBN inhibit carrageenan-induced inflammation. Inhibition of TNF-Î± production showed by decrease the value of TNF-Î± ratio. Administration EBN orally was decresed total leukocyte count and leukocyte differential count, mainly lymphocyte and basophil. On the other hand, EBN hasnât effect integumentum thick legs of mice, directly